1985
DOI: 10.1128/aem.50.1.68-80.1985
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal microbial flora after feeding phytohemagglutinin lectins (Phaseolus vulgaris) to rats

Abstract: Incorporation of purified phytohemagglutinin (PHA) lectins derived from red kidney beans (Phaseolus vulgaris) in the diet of weanling rats will cause growth failure, malabsorption of nutrients, and bacterial overgrowth in the small intestine. These effects are not caused by feeding a similar quantity of PHA to germfree rats. To define the morphological and bacterial changes on the mucosal surfaces of the jejunum, ileum, and cecum in greater detail, we pair fed two groups of weanling rats isocaloric, isonitroge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

1988
1988
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(23 citation statements)
references
References 42 publications
0
23
0
Order By: Relevance
“…That is why plant lectins are used as a potent inhibitor of gastric secretion in a dose-dependent manner without affecting pepsin secretion (Kordás et al, 2000(Kordás et al, , 2001. Mucosal damage in microvilli resulting from bacterial overgrowth is also controlled by consuming purified PHA followed by better host defence mechanism by improving the gut bacterial flora (Banwell et al, 1985;Sharon and Lis, 1989).…”
Section: Plant Lectins As Gut Stimulantsmentioning
confidence: 99%
“…That is why plant lectins are used as a potent inhibitor of gastric secretion in a dose-dependent manner without affecting pepsin secretion (Kordás et al, 2000(Kordás et al, , 2001. Mucosal damage in microvilli resulting from bacterial overgrowth is also controlled by consuming purified PHA followed by better host defence mechanism by improving the gut bacterial flora (Banwell et al, 1985;Sharon and Lis, 1989).…”
Section: Plant Lectins As Gut Stimulantsmentioning
confidence: 99%
“…In other side, it increased as well the numbers of E. coli, lactic acid bacteria, and other Enterobacteriaceae in the feces. Previously, PHA has been reported to dose-dependently induce bacterial overgrowth in the intestine, which is associated with weight loss, malabsorption, and villus damage [2,6,40]. It has been suggested that PHA increases the turnover of epithelial cells, promoting the expression of mannosylated receptor glycans on the gut surface and thus leading to increased adhesion and subsequent proliferation of mannose-sensitive type 1-fimbriated Escherichia coli.…”
Section: Discussionmentioning
confidence: 99%
“…One of these factors is phytohemagglutinin (PHA), the heat-stable lectin from the kidney bean (Phaseolus vulgaris L.; Family: Fabaceae) [1], which, when ingested orally, results in diarrhea, impaired nutrition absorption, growth rate inhibition, and can even lead to the eventual death of PHA-fed animals [2,3]. These effects are believed to result from changes in the autochthonous microflora induced by the presence of PHA in the diet [2,[4][5][6][7]. Information is accumulating on the effects of PHA on intestinal microflora, but there is a marked lack of information regarding the significance of these effects on fecal microbiota.…”
Section: Introductionmentioning
confidence: 99%
“…Recent findings support the hypothesis that the appendix serves as a safe house for human intestinal microbes, and here biofilm-like structures may have a function (Box 2, Figure 1). Several reports mention the occurrence of small agglomerates of the gut microbiota, that is, microcolonies, in the gut [31][32][33][34]. Their formation is further supported by some major theoretical concerns that argue against the formation of thick biofilms in the gut [35].…”
Section: Box 2 the Appendix As A Bacterial Safe Housementioning
confidence: 95%